2021
DOI: 10.3390/d13080346
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Diet Differences of Small Mammals in Commensal Habitats

Abstract: The stability of diversity of syntopic (inhabiting the same habitat in the same time) small mammals in commensal habitats, such as farmsteads and kitchen gardens, and, as a proxy of their diet, their isotopic niches, was investigated in Lithuania in 2019–2020. We tested whether the separation of species corresponds to the trophic guilds, whether their diets are related to possibilities of getting additional food from humans, and whether their diets are subject to seasonal trends. We analyzed diversity, dominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…This depletion in faecal δ 13 C values as compared with the diet has been also reported by other works carried out with several rodents, including the yellow-necked mouse Apodemus flavicollis [ 49 , 66 ]. Furthermore, both elemental and isotopic values found for the wood mouse in this study are consistent with the ranges found for other rodent species both in faeces [ 34 , 49 , 66 , 67 , 68 , 69 , 70 ] and hair samples [ 67 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. Furthermore, the faecal isotopic composition of wood mouse faeces found also falls within values reported in the few available scientific works addressing hair and blood isotopic composition in the wood mouse [ 51 , 52 ].…”
Section: Discussionsupporting
confidence: 89%
“…This depletion in faecal δ 13 C values as compared with the diet has been also reported by other works carried out with several rodents, including the yellow-necked mouse Apodemus flavicollis [ 49 , 66 ]. Furthermore, both elemental and isotopic values found for the wood mouse in this study are consistent with the ranges found for other rodent species both in faeces [ 34 , 49 , 66 , 67 , 68 , 69 , 70 ] and hair samples [ 67 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. Furthermore, the faecal isotopic composition of wood mouse faeces found also falls within values reported in the few available scientific works addressing hair and blood isotopic composition in the wood mouse [ 51 , 52 ].…”
Section: Discussionsupporting
confidence: 89%
“…In our context, this means that the populations of C. glareolus in the apple orchards might be augmented from the nearest habitats. However, as C. glareolus in orchards and commensal habitats are very close to human settlements [19], these aspects might be of importance in hantavirus transmission [72,73].…”
Section: Discussionmentioning
confidence: 99%
“…The bank vole (Clethrionomys glareolus), also known as Myodes glareolus [15], is a small mammal species widespread in the Palaearctic and inhabits various woodlands, shrubby areas and parklands [16]. In Lithuania, it is very widespread and numerous, found in all forest habitats, lakeshores, shrubby meadows and reedbeds [17,18], as well as agricultural and commensal habitats [14,19]. In orchards, C. glareolus can cause damage by gnawing bark [20] and, thus, knowledge of its diet might have practical significance.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the trophic ecology and diversity of small mammals among syntopic species in commensal habitats (homesteads and gardens) in the northern part of the midlatitudes was based on the first data presented in [9]. The authors aimed to determine whether the separation of species corresponds to specific trophic guilds, whether their diets are influenced by the availability of additional food from humans, and whether their diets exhibit seasonal trends.…”
mentioning
confidence: 99%